 Prove: \int_0^{\infty} x^{2n}e^{-x^2}dx=\frac{(2n)!}{2^{2n}n!}\frac{\sqrt{\pi}}{2} James Dale 2022-01-05 Answered
Prove:
$$\displaystyle{\int_{{0}}^{{\infty}}}{x}^{{{2}{n}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}={\frac{{{\left({2}{n}\right)}!}}{{{2}^{{{2}{n}}}{n}!}}}{\frac{{\sqrt{{\pi}}}}{{{2}}}}$$

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it Bernard Lacey
Alternatively, set
$$\displaystyle{I}{\left(\alpha\right)}={\int_{{0}}^{\infty}}{e}^{{-{a}{x}^{{2}}}}{\left.{d}{x}\right.}$$
differentiate n times with respect to $$\displaystyle\alpha$$ and evaluate at $$\displaystyle\alpha={1}$$
To spell things a little more out, this technique is known as Differentiation under the integral sign. Using the fact that $$\displaystyle{I}{\left(\alpha\right)}={\frac{{{1}}}{{{2}}}}\sqrt{{{\frac{{\pi}}{{\alpha}}}}}$$ and differentiating to obtain
$$\displaystyle{\frac{{{d}^{{n}}}}{{{d}{a}^{{n}}}}}{I}{\left({a}\right)}={\left(-{1}\right)}^{{n}}{\int_{{0}}^{\infty}}{x}^{{{2}{n}}}{e}^{{-{a}{x}^{{2}}}}{\left.{d}{x}\right.}$$
some algebraic manipulation and evaluating at $$\displaystyle{a}={1}$$ will yield the wanted identity.
Not exactly what you’re looking for? godsrvnt0706
Alternatively, integration by parts works immediately.
$$\displaystyle{a}_{{n}}={\int_{{0}}^{\infty}}{x}^{{{2}{n}}}{e}^{{-{x}^{{2}}}}$$
Consider $$\displaystyle{U}={x}^{{{2}{n}-{1}}}$$ so that $$\displaystyle{d}{u}={\left({2}{n}-{1}\right)}{x}^{{{2}{n}-{2}}}$$, and $$\displaystyle{d}{v}={x}{e}^{{-{x}^{{2}}}}$$ so that $$\displaystyle{V}=-{\frac{{{1}}}{{{2}}}}{e}^{{-{x}^{{2}}}}$$.
Then
$$\displaystyle{\int_{{0}}^{\infty}}{x}^{{{2}{n}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}={\frac{{{1}}}{{{2}}}}{e}^{{-{x}^{{2}}}}{x}^{{{2}{n}-{1}}}{{\mid}_{{0}}^{\infty}}-{\int_{{0}}^{\infty}}{\left({2}{n}-{1}\right)}{x}^{{{2}{n}-{2}}}{\frac{{-{1}}}{{{2}}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}$$
$$\displaystyle={\frac{{{2}{n}-{1}}}{{{2}}}}{\int_{{0}}^{\infty}}{x}^{{{2}{n}-{2}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}={\frac{{{\left({2}{n}-{1}\right)}{2}{n}}}{{{2}^{{2}}{n}}}}{\int_{{0}}^{{\infty}}}{x}^{{{2}{n}-{2}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}$$
Hence
$$\displaystyle{a}_{{n}}={\frac{{{\left({2}{n}\right)}{\left({2}{n}-{1}\right)}}}{{{2}^{{2}}{n}}}}{a}_{{{n}-{1}}}$$
and since $$\displaystyle{a}_{{0}}={\frac{{\sqrt{{\pi}}}}{{{2}}}}$$ we conclude
$$\displaystyle{a}_{{n}}={\int_{{0}}^{\infty}}{x}^{{{2}{n}}}{e}^{{-{x}^{{2}}}}{\left.{d}{x}\right.}={\frac{{{\left({2}{n}\right)}!}}{{{2}^{{{2}{n}}}{n}!}}}{\frac{{\sqrt{{\pi}}}}{{{2}}}}$$ star233

Let's suppose that, one way or another, you know that $$\int_{-\infty}^{\infty} e^{-x^2}dx=\sqrt{\pi}$$. Then
$$\int_{-\infty}^\infty e^{2tx-x^2}dx=e^{t^2}\int_{-\infty}^\infty e^{-(t-x)^2}dx=e^{t^2}\sqrt{\pi}$$
On the other hand,
$$\int_{-\infty}^\infty e^{2tx-x^2}dx=\int_{-\infty}^{\infty}(\sum_{n\geq0}\frac{2^nt^nx^n}{n!})e^{-x^2}dx=\sum_{n\geq0}\frac{2^nt^n}{n!}\int_{-\infty}^{\infty}x^ne^{-x^2}dx$$
Finally, note that by evenness,
$$\int_{-\infty}^\infty x^{2n}e^{-x^2}dx=2\int_0^\infty x^{2n}e^{-x^2}dx$$